2018
DOI: 10.1016/j.jecp.2018.03.009
|View full text |Cite
|
Sign up to set email alerts
|

The redeployment of attention to the mouth of a talking face during the second year of life

Abstract: Previous studies have found that when monolingual infants are exposed to a talking face speaking in a native language, 8- and 10-month-olds attend more to the talker's mouth, whereas 12-month-olds no longer do so. It has been hypothesized that the attentional focus on the talker's mouth at 8 and 10 months of age reflects reliance on the highly salient audiovisual (AV) speech cues for the acquisition of basic speech forms and that the subsequent decline of attention to the mouth by 12 months of age reflects the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 59 publications
3
50
0
Order By: Relevance
“…The diminished attention to a speaker's mouth region finding in ASD replicates earlier work across other laboratories, ages, and tasks (Chawarska & Shic, 2009;Chawarska et al, 2012;Hosozawa et al, 2012;Irwin & Brancazio, 2014;Johnels, Gillberg, Falck-Ytter, & Miniscalco, 2014;Nakano et al, 2010). In TD children, access to redundant oro-motor cues is known to play an important role in language acquisition and speech processing and diminished mouth looking in toddlers is associated with later language disadvantages (de Boisferon et al, 2018;Sumby & Pollack, 1954;Tenenbaum et al, 2014). Our work is consistent with this phenomenon, both categorically (in terms of differences observed between TD toddlers and the more language-impaired toddlers with ASD) and dimensionally (in terms of the association between decreased face looking when speech cues are present and verbal ability evident in the ASD group).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The diminished attention to a speaker's mouth region finding in ASD replicates earlier work across other laboratories, ages, and tasks (Chawarska & Shic, 2009;Chawarska et al, 2012;Hosozawa et al, 2012;Irwin & Brancazio, 2014;Johnels, Gillberg, Falck-Ytter, & Miniscalco, 2014;Nakano et al, 2010). In TD children, access to redundant oro-motor cues is known to play an important role in language acquisition and speech processing and diminished mouth looking in toddlers is associated with later language disadvantages (de Boisferon et al, 2018;Sumby & Pollack, 1954;Tenenbaum et al, 2014). Our work is consistent with this phenomenon, both categorically (in terms of differences observed between TD toddlers and the more language-impaired toddlers with ASD) and dimensionally (in terms of the association between decreased face looking when speech cues are present and verbal ability evident in the ASD group).…”
Section: Discussionsupporting
confidence: 76%
“…In the same context, young children with ASD were reported to look at the eyes a similar proportion of time as TD and DD controls, (Chawarska et al, 2012;Moriuchi et al, 2016;Nakano et al, 2010) or language-delayed controls; (Hosozawa et al, 2012) though others report less looking at the eye area in toddlers with ASD than in controls (Jones et al, 2008). Considering the importance of the eye region as a source of information regarding attentional and affective states of others (Guarnera, Hichy, Cascio, & Carrubba, 2015) and of the mouth region for providing cues relevant to speech perception, (de Boisferon, Tift, Minar, & Lewkowicz, 2018) factors that affect attention to these features deserve further investigation.…”
Section: Introductionmentioning
confidence: 98%
“…First, under the language expertise hypothesis, we predicted a u-shaped developmental pattern, whereby children would show initial interest in the eyes, followed by greater interest in the mouth, and then an increase in interest to the eyes again around age 12 months (Lewkowicz & Hansen-Tift, 2012;Pons et al, 2015). Instead, we observed more of an asymptotic pattern, which confirmed an initially stronger interest in the eyes at 5 months relative to older ages Frank et al, 2012;Hillairet de Boisferon et al, 2017;Hunnius & Geuze, 2004;Pons et al, 2015;Tenenbaum et al, 2013;Wagner, Luyster, Yim, Tager-Flusberg, & Nelson, 2013), followed by an increase in attention to the mouth (Frank et al, 2012;Hillairet de Boisferon et al, 2018;Pons et al, 2018;Tenenbaum et al, 2013) that persisted until age 5 years. While 12-month-olds' interest in the mouth was not always as robust as at adjacent ages (see also Lewkowicz & Hansen-Tift, 2012;Pons et al, 2015), we did not find statistically significant differences with adjacent age bins, and thus our data lack support for a developmental shift at 12 months as has been previously reported (Lewkowicz & Hansen-Tift, 2012;Pons et al, 2015).…”
Section: Discussionmentioning
confidence: 70%
“…Other studies of bilingual infants also have found that they attend more to a talker's mouth than eyes than do monolingual infants (Ayneto & Sebastián‐Gallés, ; Fort et al., ). Finally, a study of 14‐ and 18‐month‐old monolingual infants’ selective attention to talking faces (Hillairet de Boisferon, Tift, Minar, & Lewkowicz, ) has found that, at these ages, monolingual infants attend more to a talker's mouth in response to native and non‐native speech. Considered together, these findings suggest that infants continue to rely on the redundantly specified audiovisual speech cues when they are cognitively challenged by having to acquire two languages as well as when they face the challenging task of having to acquire a brand‐new lexicon during the latter part of the second year of life (Hillairet de Boisferon et al., ).…”
Section: Discussionmentioning
confidence: 99%